Influence of coating dental enamel with a TiF4-loaded polymeric primer on the adverse effects caused by a bleaching gel with 35% H2O2 - Peruchi, Victória [UNESP]; Ribeiro, Rafael Antonio de Oliveira [UNESP]; Mendes Soares, Igor Paulino [UNESP]; Oliveira Fernandes, Lídia de [UNESP]; de Oliveira, Juliana Rios [UNESP]; Pires, Maria Luiza Barucci Araújo [UNESP]; Hebling, Josimeri [UNESP]; Soares, Diana Gabriela; de Souza Costa, Carlos Alberto [UNESP] (Elsevier, 2024)
Objective: To evaluate whether coating enamel with a polymeric primer (PPol) containing titanium tetrafluoride (TiF4) before applying a bleaching gel with 35% H2O2 (35% BG) increases esthetic efficacy, prevents changes in morphology and hardness of enamel, as well as reduces the cytotoxicity from conventional in-office bleaching. Materials and methods: Standardized enamel/dentin discs were stained and bleached for 45 min (one session) with 35% BG. Groups 2TiF4, 6TiF4, and 10TiF4 received the gel on the enamel previously coated with PPol containing 2 mg/mL, 6 mg/mL, or 10 mg/mL, respectively. No treatment or application of 35% BG directly on enamel were used as negative control (NC), and positive control (PC), respectively. UV-reflectance spectrophotometry (CIE L*a*b* system, ΔE00, and ΔWI, n = 8) determined the bleaching efficacy of treatments. Enamel microhardness (Knoop, n = 8), morphology, and composition (SEM/EDS, n = 4) were also evaluated. Enamel/dentin discs adapted to artificial pulp chambers (n = 8) were used for trans-amelodentinal cytotoxicity tests. Following the treatments, the extracts (culture medium + bleaching gel components diffused through the discs) were collected and applied to odontoblast-like MDPC-23 cells, which were assessed concerning their viability (alamarBlue, n = 8; Live/Dead, n = 4), oxidative stress (n = 8), and morphology (SEM). The amount of H2O2 in the extracts was also determined (leuco crystal violet/peroxidase, n = 8). The numerical data underwent one-criterion variance analysis (one-way ANOVA), followed by Tukey's test, at a 5% significance level. Results: Regarding the ΔE00, no difference was observed among groups 2TiF4, 6TiF4, and PC (p > 0.05). The ΔWI was similar between groups 2TiF4 and PC (p > 0.05). The ΔWI of group 6TiF4 was superior to PC (p < 0.05), and group 10TiF4 achieved the highest ΔE00 and ΔWI values (p < 0.05). Besides limiting enamel microstructural changes compared to PC, group 10TiF4 significantly increased the hardness of this mineralized dental tissue. The highest cellular viability occurred in 10TiF4 compared to the other bleached groups (p < 0.05). Trans-amelodentinal H2O2 diffusion decreased in groups 2TiF4, 6TiF4, and 10TiF4 in comparison with PC (p < 0.05). Conclusion: Coating enamel with a PPol containing TiF4 before applying a 35% BG may increase enamel microhardness and esthetic efficacy and reduce the trans-amelodentinal cytotoxicity of conventional in-office tooth bleaching. The PPol containing 10 mg/mL of TiF4 promoted the best outcomes.
Keywords: Catalysis; Odontoblasts; Tooth bleaching; Toxicity